Anatomic Understanding of Vertical Hemispherotomy With Cadaveric Brains and Intraoperative Photographs. Issue 4 (28th May 2016) - Uda, Takehiro; Tamrakar, Samantha; Tsuyuguchi, Naohiro; Kawashima, Toshiyuki; Goto, Hiroyuki; Nakajo, Kosuke; Umaba, Ryoko; Sato, Hidetoshi; Ohata, Kenji
Abstract : BACKGROUND: Vertical hemispherotomy is performed in hemispheric epilepsy to disconnect commissural fibers, projecting fibers, and limbic system from the affected side of the brain with minimal parenchyma removal. However, anatomic understanding of this surgery is generally difficult. OBJECTIVE: To present the vertical hemispherotomy procedures using cadaveric brains and intraoperative photographs. METHODS: Two formalin-fixed adult cadaveric brains were used to demonstrate vertical hemispherotomy. Intraoperative photographs were taken of a 19-year-old man with intractable epilepsy due to head trauma in infancy. RESULTS: After coronal skin incision along the coronal suture, bifrontal craniotomy and a C-shaped dural incision from lateral to medial to the midline are performed. The interhemispheric fissure is dissected from anterior to posterior. Interhemispheric total corpus callosotomy is performed to disconnect commissural fibers. Corticotomy on the cingulate gyrus is performed to approach the lateral ventricle. The lateral border of the thalamus is cut from posterior to anterior until exposing the inferior horn of the lateral ventricle and hippocampal head to disconnect projecting fibers. At the anteromedial side of the hippocampus, the inferior part of the amygdala and uncal gyrus is removed, exposing the basal cistern to disconnect the hippocampus and amygdala. The posterior column of the fornix at the trigone of the lateral ventricle is resected to disconnect the limbic system. Projecting fibers from the anterior frontal lobe are disconnected. CONCLUSION: A step-by-step procedure using cadaveric brains and intraoperative photographs provide a better anatomic understanding of vertical hemispherotomy.